Peningkatan Hasil Belajar Peserta Didik pada Pembelajaran IPAS menggunakan Model Discovery Learning berbantuan Media Flipbook di Kelas V SDN 1 Padang Panjang Timur - Aulia, Dina; Arwin, Arwin (TSAQOFAH, 2025)
This study is motivated by the low learning outcomes of students in the subject of Natural and Social Sciences (IPAS), highlighting the need for innovation in instructional strategies. The objective of this research is to describe the implementation of the Discovery Learning model assisted by Flipbook media to improve the learning outcomes of fifth-grade students at SDN 1 Padang Panjang Timur. The research employs a Classroom Action Research (CAR) method using both qualitative and quantitative approaches, conducted over two cycles. Each cycle consisted of the stages of planning, implementation, observation, and reflection. Cycle I was carried out over two sessions, while Cycle II consisted of one session. The research subjects included one teacher and 28 fifth-grade students, comprising 16 boys and 12 girls. Data were collected through observation, tests, and non-test techniques. The findings indicate significant improvements across various aspects of learning. Observation of the teaching module increased from 87.49% (categorized as good) in Cycle I to 97.72% (very good) in Cycle II. Teacher and student activity also rose from 82.81% to 93.75%. The average student learning outcome improved from 74.99 (fair category) in Cycle I to 86.07 (good category) in Cycle II. The study concludes that the implementation of the Discovery Learning model assisted by Flipbook media is effective in enhancing student learning outcomes in IPAS instruction.